Gut-Derived Sterile Inflammation and Parkinson's Disease - Shannon, Kathleen M. (Frontiers in Neurology, 2022)
The etiology of Parkinson's disease (PD) is unknown, but evidence is increasing that there is a prominent inflammatory component to the illness. Epidemiological, genetic and preclinical evidence support a role for gut-derived sterile inflammation. Pro-inflammatory bacteria are over-represented in the PD gut microbiota. There is evidence for decreased gut barrier function and leak of bacterial antigen across the gut epithelium with submucosal inflammation and systemic exposure to the bacterial endotoxin lipopolysaccharide. Preclinical evidence supports these clinical findings and suggests that systemic inflammation can affect the CNS through vagal pathways or the systemic circulation. We will review recent preclinical and clinical evidence to support this mechanism and suggest possible treatments directed at the gut-brain axis.